2001
DOI: 10.1021/bm015574q
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-Installed Block Copolymer Micelles:  Their Preparation and Specific Interaction with Lectin Molecules

Abstract: Several types of sugar-installed poly(ethylene glycol)/poly(DL-lactide) (sugar-PEG/PLA) block copolymers were synthesized. The synthesized block copolymer forms a core-shell type polymeric micelle in aqueous media possessing sugar molecules on its surface. Specific recognition of lectin proteins with the sugar molecules on the micelle surface was observed. Both the galactose- and lactose-installed micelles specifically interacted with RCA-1; on the other hand the mannose-installed micelle interacted specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(103 citation statements)
references
References 27 publications
1
101
1
Order By: Relevance
“…The attachment of various specifi c ligands to the water-exposed termini of hydrophilic blocks could be used to improve the targeting of micelles and micelle-incorporated drugs and DNA. 115 Among those ligands are various sugar moieties, 116 transferrin, 117 and folate residues 118 since many target cells, especially cancer cells, overexpress appropriate receptors (eg, transferrin and folate receptors) on their surface. Thus, it was shown that galactose-and lactose-modifi ed micelles made of PEG-polylactide copolymer specifi cally interact with lectins, thus modeling targeting delivery of the micelles to hepatic sites.…”
Section: Tumor-targeted Specifi C Ligands On Long-circulating Nanocarmentioning
confidence: 99%
“…The attachment of various specifi c ligands to the water-exposed termini of hydrophilic blocks could be used to improve the targeting of micelles and micelle-incorporated drugs and DNA. 115 Among those ligands are various sugar moieties, 116 transferrin, 117 and folate residues 118 since many target cells, especially cancer cells, overexpress appropriate receptors (eg, transferrin and folate receptors) on their surface. Thus, it was shown that galactose-and lactose-modifi ed micelles made of PEG-polylactide copolymer specifi cally interact with lectins, thus modeling targeting delivery of the micelles to hepatic sites.…”
Section: Tumor-targeted Specifi C Ligands On Long-circulating Nanocarmentioning
confidence: 99%
“…Thus, covalent attachment of cell specific ligands, e.g. monoclonal antibodies [384], sugars [385], folate residues [386], and peptides [387] on the surface of polymeric micelles has been pursued to enhance drug delivery to various cells.…”
Section: Complexing Targeting Ligand Molecules To Micellesmentioning
confidence: 99%
“…A galactose-bearing PEG-PLA micelle was confirmed to selectively attach to RCA-1 lectin (RCA-1 is one of the well-studied plant lectins which specifically recognize a β-D-galactose residue). Nagasaki et al in another study synthesized several types of sugar-installed PEG-PLA block copolymers which formed polymeric micelles in aqueous media [385]. Specific recognition of lectin proteins with the sugar molecules on the micelle surface was observed.…”
Section: Sugarsmentioning
confidence: 99%
“…[63][64][65][66][67] The PEG block forms a stericstabilization layer, while the cationic block encapsulates the DNA in the core of the micelle. In endocytosis, the encapsulated DNA gains entry into a cell without passing through the cell membrane.…”
Section: Dna Condensationmentioning
confidence: 99%